TH1-Polarized TFH Cells Delay Naturally-Acquired Immunity to Malaria - Yap, Xi Zen; Hustin, Lucie S. P.; Sauerwein, Robert W. (Frontiers in Immunology, 2019)
Humoral immunity is a critical effector arm for protection against malaria but develops only slowly after repeated infections. T cell-mediated regulatory dynamics affect the development of antibody responses to Plasmodium parasites. Here, we hypothesize that T follicular helper cell (TFH) polarization generated by repeated Plasmodium asexual blood-stage infections delays the onset of protective humoral responses. IFN-γ production promotes polarization towards TFH1 and increased generation of regulatory follicular helper cells (TFR). Delineating the mechanisms that drive TH1 polarisation will provide clues for appropriate induction of lasting, protective immunity against malaria.